2011
DOI: 10.1002/pola.24890
|View full text |Cite
|
Sign up to set email alerts
|

A novel protocol for the preparation of uniform polymer microspheres with high yields through step polymerization of isophorone diisocyanate

Abstract: Uniform polymer microspheres with neat surface are of high interests. Precipitation polymerization of vinylic monomers remains a very limited process owing to very low monomer concentration allowed. Here, a fully novel protocol for the production of uniform polymeric microspheres is presented. Using one single monomer, isophorone diisocyanate, highly monodisperse polyurea microspheres were achieved with very high yield in a very short time period via precipitation polymerization in water-acetone mixed solvent.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…Polyureas (PU) can be synthesized either through condensation polymerization of multifunctional isocyanates (NCO, commonly diisocyanate or triisocyanate) with polyamines, or through the reaction of multifunctional isocyanate in excess with water with release of carbon dioxide, which turns the isocyanate groups into amines, followed by the same condensation polymerization of the isocyanate with the in situ produced amines. [1][2][3] PU has been well known to have thermal shock and abrasion resistance, high impact resistance, good exibility and water repellency as well as fast curing etc. 4 Common applications are protective coating materials for different structural materials, including concrete 5,6 and metals, [7][8][9] for instance.…”
Section: Introductionmentioning
confidence: 99%
“…Polyureas (PU) can be synthesized either through condensation polymerization of multifunctional isocyanates (NCO, commonly diisocyanate or triisocyanate) with polyamines, or through the reaction of multifunctional isocyanate in excess with water with release of carbon dioxide, which turns the isocyanate groups into amines, followed by the same condensation polymerization of the isocyanate with the in situ produced amines. [1][2][3] PU has been well known to have thermal shock and abrasion resistance, high impact resistance, good exibility and water repellency as well as fast curing etc. 4 Common applications are protective coating materials for different structural materials, including concrete 5,6 and metals, [7][8][9] for instance.…”
Section: Introductionmentioning
confidence: 99%
“…Whether the reaction temperature goes up or down, the uniformity of PEA microspheres gets worse. Obviously, polymerization at higher temperature has dual effects on the formation of the microspheres: enhancing the polymerization rate to accelerate the turbidity appearance, and increasing the solubility of the oligomers, entraining therefore a delayed observation of the turbidity 23 . For the preparation of PEA microspheres, the turbidity appearance was effectively advanced from 165 to 125 minutes with a slightly increased oligomers from 22.46 to 24.54 wt%, when polymerization temperature gone up from −18°C to 4°C and further to 30°C, indicating that the impact of increasing polymerization temperature to enhancing the polymerization rate was more important compared with its effect on increased solubility of the formed oligomers.…”
Section: Resultsmentioning
confidence: 99%
“…However, commercially available monomers for them are too little to endow microspheres with ideal property, making it is difficult to obtain functional groups on the particle surface to meet different requirements for practical applications. Precipitation polymerizations of multi‐functional isocyanates with water, amino or hydroxyl compounds are systematic studied by our group and various solid and porous polyurea or polyurethane beads were obtained 23‐25 . Those particles were widely used as dyes degradation 26 and metal ions absorption, 27,28 and applied as supports of Pd 24,29 and Au 30,31 catalysts, benefiting of their functional surface with abundant amino groups.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the reactivity of amines is much higher than that of water in reaction towards isocyanate [10,[14][15][16][17]. Therefore, different reactions took place when TDI was added to EDA aqueous solution.…”
Section: Mechanism Of Pu Formation By Tdi Reactionsmentioning
confidence: 95%